Effects of a Mobile Application to Improve Oral Hygiene in Children - Serap Sinan Özvarış; Dilşah Çoğulu (Galenos Yayinevi, 2024)
Aim: Dental caries is one of the most common chronic diseases which affects oral health. Tooth brushing is considered the most effective method of preventing dental caries. Providing this motivation and ensuring this habit can be difficult, especially in children. Novel methods for improving tooth brushing habits are desired. This study aimed to investigate a mobile application's effectiveness in improving oral health in children. Materials and Methods: Two hundred children between 5-12 years old who applied to the Department of Pedodontics, Ege University Faculty of Dentistry, for routine dental examination were included in this study. Children who had any systemic, physical, and/or mental disorders or those who had emergency dental complaints were not included in this study. A structured questionnaire including the child's oral hygiene habits was completed by the parents. In the clinical examination, the caries indices (DMFT/dmft and DMFS/dmfs), dental plaque, and gingival index scores of the children were recorded. Following this clinical examination, the "Brush DJ" mobile application was introduced to the children and their parents. After the first examination, the children were referred for their dental treatment and all were recalled after three months. At the recall examination, a second questionnaire was completed by the parents. The dental caries index (DMFT/dmft and DMFS/dmfs) scores, dental plaque, and gingival index scores were recorded again. A parental satisfaction questionnaire was administered to the parents. Statistical analysis was carried out using the SPSS 25.0 software program. The compliance of the parameters to the normal distribution was evaluated via the Shapiro-Wilk test. The Mann-Whitney U and Kruskal-Wallis tests were used for comparisons between the groups. For intra-group comparisons, the Wilcoxon test, chi-square test, Fisher's Exact test, and t-test were used. The results were evaluated at a 95% confidence interval and a statistical significance level of p<0.05. Results: It was determined that 56.5% (n=113) of the children participating in this study were girls and 43.5% (n=87) were boys. One hundred and seventy-one of the 200 children were reported to be using the mobile application. It was observed that the tooth brushing frequency increased in 97 children due to their use of the mobile application. It was also observed that the tooth brushing duration increased in 143 of 171 children as a result of their use of the application. Initial plaque and gingival index scores (1.59±0.40; 1.18±0.40, respectively) were statistically higher than the recall examination scores (1.29±0.46; 1.09±0.49 respectively) (p<0.05). Based on the parental satisfaction survey data, it was observed that the use of the mobile app was effective in improving tooth brushing habits, and brushing became more regular and enjoyable in all children. Conclusion: It was concluded that using the "Brush DJ" mobile tooth brushing app is effective in improving oral hygiene habits and making it a regular behavior in children. Long-term follow-up studies with a larger number of subjects comparing different oral hygiene education methods should be planned.